2015
DOI: 10.3136/fstr.21.231
|View full text |Cite
|
Sign up to set email alerts
|

Green Rooibos Extract from <i>Aspalathus linearis</i>, and its Component, Aspalathin, Suppress Elevation of Blood Glucose Levels in Mice and Inhibit α-amylase and α-glucosidase Activities <i>in vitro</i>

Abstract: To evaluate the suppressive effects of green rooibos (Aspalathus linearis) unfermented tea on postprandial hyperglycemia, we orally administered four carbohydrates with or without green rooibos extract (GRE) and its major flavonoid aspalathin (Asp). GRE significantly suppressed the elevation of blood glucose levels after glucose, maltose, and starch intake. Asp also lowered the levels for all four carbohydrates. To clarify the mechanism underlying these results, we performed an intraperitoneal glucose toleranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
2
9
1
Order By: Relevance
“…A similar outcome was reported by Muller et al [74], where it was showed that an aspalathin-enriched unfermented rooibos extract and pure aspalathin modulates glucose metabolism by inhibiting the activity of α-glucosidase (from Saccharomyces cerevisae ) and promoting glucose uptake in C2C12 muscle cells while also reducing fasting plasma glucose in STZ-induced diabetic Wistar rats. Consistent with this evidence, Mikami et al [75] reported that both unfermented rooibos and aspalathin suppressed the elevation of blood glucose that was induced by carbohydrate overload in non-diabetic rats and inhibit the activity of α-amylase and α-glucosidase enzymes (determined as maltase and sucrase from rat intestine), suggesting that this effect is due to the ability of rooibos and aspalathin to inhibit glucose metabolism. Using the same C2C12 muscle cells model, Mazibuko et al [76], reported that a fermented and an aspalathin-enriched unfermented rooibos extract, both ameliorated palmitate-induced insulin resistance by increasing glucose uptake, mitochondrial activity and ATP production.…”
Section: South African Herbal Tisanesmentioning
confidence: 68%
“…A similar outcome was reported by Muller et al [74], where it was showed that an aspalathin-enriched unfermented rooibos extract and pure aspalathin modulates glucose metabolism by inhibiting the activity of α-glucosidase (from Saccharomyces cerevisae ) and promoting glucose uptake in C2C12 muscle cells while also reducing fasting plasma glucose in STZ-induced diabetic Wistar rats. Consistent with this evidence, Mikami et al [75] reported that both unfermented rooibos and aspalathin suppressed the elevation of blood glucose that was induced by carbohydrate overload in non-diabetic rats and inhibit the activity of α-amylase and α-glucosidase enzymes (determined as maltase and sucrase from rat intestine), suggesting that this effect is due to the ability of rooibos and aspalathin to inhibit glucose metabolism. Using the same C2C12 muscle cells model, Mazibuko et al [76], reported that a fermented and an aspalathin-enriched unfermented rooibos extract, both ameliorated palmitate-induced insulin resistance by increasing glucose uptake, mitochondrial activity and ATP production.…”
Section: South African Herbal Tisanesmentioning
confidence: 68%
“…Consistent with these findings, Muller et al [140] showed that an aspalathin-rich green rooibos extract and pure aspalathin are able to modulate glucose metabolism by inhibiting α-glucosidase enzyme activity and promoting glucose uptake in pancreatic and skeletal muscle cells as well as improving glucose tolerance in streptozotocin-induced diabetic Wistar rats. Mikami et al [141] demonstrated that green rooibos extract and aspalathin were effective at reducing blood glucose levels of nondiabetic mice following ingestion of glucose, sucrose, and starch solutions, while suppressing the activities of α-glucosidase and α-amylase, key enzymes involved in carbohydrate hydrolysis. Mazibuko et al [92,142] further investigated the molecular mechanisms associated with the ameliorative effect of pure aspalathin and an aspalathin-rich green rooibos extract on palmitate-induced insulin resistance in C2C12 myotubes and 3T3-L1 adipocytes.…”
Section: Effect Of Aspalathin On Glucose and Lipid Metabolismmentioning
confidence: 99%
“…35 They further added that rooibos, in a dose-dependent manner, enhanced glucose uptake in cultured L6 myotubes and also increased the secretion of insulin by RIN-5F cells. The results of Kawano et al are supported by several other authors [36][37][38][39][40][41] with the inclusion that aspalathin promoted activated protein kinase (AMPK) phosphorylation, enhanced GLUT4 translocation and also improved protein kinase B activation. This suggests that rooibos may improve glucose metabolism by enhancing glucose uptake and restoring normal insulin signalling.…”
Section: Introductionmentioning
confidence: 77%